Handbook of federal countries, 2005 - Griffiths, Ann Lynn, 1960-; Nerenberg, Karl (Published for Forum of Federations/Forum des fédérations by McGill-Queen's University Press, 2005)
"As a project of the Forum of Federations, an international network seeking to strengthen democratic governance through federal values, practices, and principles, Handbook of Federal Countries, 2005 is an essential sourcebook of information, with maps and statistical tables in each chapter and sources readers can consult for more information."--Jacket